49‐1: Invited Paper: Analog LCOS SLM Devices for Display Applications. Issue 1 (29th May 2019) - Fan-Chiang, Kuan-Hsu; Wang, Hsing-Lung; Li, Yuet-Wing; Tsai, Hsien-Chang
Abstract : Liquid‐crystal‐on‐silicon (LCOS) device is a potential candidate for spatial light modulators (SLMs) due to its high resolution and the wide range of tunable phase retardation. Besides the telecom applications, SLM is also very promising for display applications, especially for the augmented reality (AR) displays. In this paper, we will discuss the advantages of analog LCOS SLM compared with the digital one. A 0.6" short‐loop sample test result with precise cell gap controlled is introduced. Some CGH images are demonstrated using different algorithms. Finally, the liquid crystal response time performances are also discussed.